SCAR AFTER SURGICAL INCISION FOR APPENDECTOMY: S-SHAPE VS LINEAR INCISION - M OMRANI FARD; M NOURI (Journal of Research in Medical Sciences, 2003)
Introduction: Hyperthrophic scar and keloid is a big problem after many operation. Hypertrophic scar depended on many factor one of them is Incision.
Method: This is a randomized clinical trial and sequential sampling in Alzahra hospital and Kashani hospital. we selected two groups, one group we used S shape incision and observed group linear incision. Age was between 10-30 years and dermatological problems and cigaret smoking was Negative in two groups perforated and secondly skin closure was excluded in our study. patient divided in two group each group was twenty and fllowed for one year. Patients satisfaction and skin collor normality and itchiny was evaluated in two groups.
Results: Appearance of scar was different in collor much and shape. Normality for collor of incision in s shape groups were 68.4% but in linar incision was 31.6% (Pvalue= 0.026) with statically meaningful. Mean of scar width: In 5-shape =1.33+0.49mm in Linear shape = 2.23+0.92. P = 0.001. Prevalence of itching was same in both groups.
Discussion: patients overall satisfaction and itching were the same for both groups. skin color normality was 68.4% in 5 shape incision groups versus 31.6% in linear incision groups which has been shown to be statistically meaningful using chi-square test so it seems reasonable to conclude that calor mathing is more favorable in 5 shape incisions rather than linear incision. Mean of scare width in licear incision group was 2.23+0.92 mm versus 1.32+0.49 mm in 5 shape incision group. this difference is also statistically meaningful using T test. 50 it can be concluded that using 5 shape incision is better because post operative scar is smaller and exposure is like linear incision.